(x-3)(5+2x)-(x-3)(x-6)=

Simple and best practice solution for (x-3)(5+2x)-(x-3)(x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(5+2x)-(x-3)(x-6)= equation:


Simplifying
(x + -3)(5 + 2x) + -1(x + -3)(x + -6) = 0

Reorder the terms:
(-3 + x)(5 + 2x) + -1(x + -3)(x + -6) = 0

Multiply (-3 + x) * (5 + 2x)
(-3(5 + 2x) + x(5 + 2x)) + -1(x + -3)(x + -6) = 0
((5 * -3 + 2x * -3) + x(5 + 2x)) + -1(x + -3)(x + -6) = 0
((-15 + -6x) + x(5 + 2x)) + -1(x + -3)(x + -6) = 0
(-15 + -6x + (5 * x + 2x * x)) + -1(x + -3)(x + -6) = 0
(-15 + -6x + (5x + 2x2)) + -1(x + -3)(x + -6) = 0

Combine like terms: -6x + 5x = -1x
(-15 + -1x + 2x2) + -1(x + -3)(x + -6) = 0

Reorder the terms:
-15 + -1x + 2x2 + -1(-3 + x)(x + -6) = 0

Reorder the terms:
-15 + -1x + 2x2 + -1(-3 + x)(-6 + x) = 0

Multiply (-3 + x) * (-6 + x)
-15 + -1x + 2x2 + -1(-3(-6 + x) + x(-6 + x)) = 0
-15 + -1x + 2x2 + -1((-6 * -3 + x * -3) + x(-6 + x)) = 0
-15 + -1x + 2x2 + -1((18 + -3x) + x(-6 + x)) = 0
-15 + -1x + 2x2 + -1(18 + -3x + (-6 * x + x * x)) = 0
-15 + -1x + 2x2 + -1(18 + -3x + (-6x + x2)) = 0

Combine like terms: -3x + -6x = -9x
-15 + -1x + 2x2 + -1(18 + -9x + x2) = 0
-15 + -1x + 2x2 + (18 * -1 + -9x * -1 + x2 * -1) = 0
-15 + -1x + 2x2 + (-18 + 9x + -1x2) = 0

Reorder the terms:
-15 + -18 + -1x + 9x + 2x2 + -1x2 = 0

Combine like terms: -15 + -18 = -33
-33 + -1x + 9x + 2x2 + -1x2 = 0

Combine like terms: -1x + 9x = 8x
-33 + 8x + 2x2 + -1x2 = 0

Combine like terms: 2x2 + -1x2 = 1x2
-33 + 8x + 1x2 = 0

Solving
-33 + 8x + 1x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-11 + -1x)(3 + -1x) = 0

Subproblem 1

Set the factor '(-11 + -1x)' equal to zero and attempt to solve: Simplifying -11 + -1x = 0 Solving -11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -1x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 0 + 11 -1x = 0 + 11 Combine like terms: 0 + 11 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-11, 3}

See similar equations:

| (5x-1)/3=3 | | 2x+30=2x-30 | | 9s(7s+7)+s(3s+6)= | | 4-5[2-(4y-3)]= | | (2x+4)+(4x-15)+93=180 | | b=80+(25+7)6 | | b=80+(25+7)3 | | 20.5=13+x | | Q=v/x | | =3x^2-10 | | 3x+(3x-48)+(2x-36)=180 | | 32-8w=8 | | (x+15)+(x+42)+89=180 | | =x^3-5x^2+x | | (x-29)+(x+32)+37=180 | | (9n+6m)+(7m+3)+(-2-4n)= | | 3+-10x=4+x | | 3b=11/2 | | =3x^2-10x | | 6(2-x/6=1 | | (2x-15)+(3x+10)+2x=180 | | 3(4-1)-7x=17 | | 6(7x+7)=-6(x+1) | | 4x-5[4(x+3)-(x-2)]-5= | | (r-2)(r+10)=-9 | | X-5/14=4/7 | | 1-(2)/(5)y=4x-3 | | (4x-28)+(9x-17)+30=180 | | (7+7d)+(-5+9m)= | | 2.2x=12.76 | | 6.3k-1.4+3.5=52.5 | | -(2k+4)-4(k+4)=4k-8k |

Equations solver categories